2018
DOI: 10.1111/jne.12604
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in hypothalamic synaptophysin and death markers may be associated with vasopressin impairment in sepsis survivor rats

Abstract: The impairment in arginine vasopressin (AVP) secretion during sepsis is described in clinical and experimental studies and has been associated with oxidative stress, apoptosis, and diminished activation of hypothalamic neurons. Few studies have, however, assessed these abnormalities in sepsis survivors. Here we performed two sets of experiments on Wistar rats that had been subjected to sepsis by cecal ligation and puncture (CLP) or nonmanipulated (naive) as control. In the first set, tissues and blood were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
5
8
0
1
Order By: Relevance
“…cannula. The inflammation process has been shown to impair both AVP and OT secretion . On the other hand, in the present study, the hypertonic EVE was able to increase both AVP and OT plasma levels as expected.…”
Section: Discussionsupporting
confidence: 82%
“…cannula. The inflammation process has been shown to impair both AVP and OT secretion . On the other hand, in the present study, the hypertonic EVE was able to increase both AVP and OT plasma levels as expected.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study revealed that 10 days after sepsis induction, no sepsis signals could be observed in the plasma and the contents of inflammatory mediators in the plasma were similar to those of the control group. 80 Our results further confirmed these findings by showing that the serum contents of inflammatory mediators showed no differences among the three groups.…”
Section: Discussionsupporting
confidence: 85%
“…Recently, a decrease in synaptophysin and PSD95 expression was described following neuroinflammation induced by the cecal ligation and puncture (CLP) model of sepsis [ 77 , 78 ] or after intraperitoneally administration of LPS—a component of Gram-negative bacteria [ 79 82 ]. There are few studies that correlate infection during gestation and disturbance of synaptophysin expression in the offspring and none using bacterial sepsis models.…”
Section: Discussionmentioning
confidence: 99%